Influence of 3D printed structures on energy absorption ability of brittle polymers under dynamic cyclic loading - Mohit Sood; Chang-Mou Wu (eXPRESS Polymer Letters)
Structural change can alter the energy absorption ability of constituent materials. Carbon organic framework (COF)-inspired structures printed with fusion deposition modeling (FDM) using polylactic acid (PLA) and acrylonitrile butadiene styrene (ABS) polymers are used to analyze the structural effect. Structures were characterized for specific energy absorption under static compression. The best structures from the static testing results were further characterized for dynamic compression using sinusoidal displacement to calculate the dynamic elastic recovery (DER), hysteresis work, and tan δ. Based on the results, the bending-dominated structure absorbed the highest energy, and the surface structure provided the best DER. The structure which failed by the pure collapsing of the layer showed the best specific values. The delamination of printed layers during loading reduced the performance of structures despite of the materials.